Studi Islam Pendekatan Sains: Relevansi Wahyu terhadap Ilmu Pengetahuan Modern - Warto, W (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2018)
Each prophet is given a miracle according to the needs and conditions of his people. If the previous prophet was sent by Allah SWT only for certain people, a certain period, and strengthened by materialistic miracles such as the staff of Moses and others, then scientific miracles are very relevant to the people and the present age. This is the greatest scientific miracle in the history of human life. Allah wants every piece of information conveyed by the Koran to materialize someday. When an event and event occurs in accordance with the Koran, the miracle is revealed. So this scientific miracle is always new every time. In the present era, the truth of Islamic science began to unfold. These scientific truths will one day attract humanity to acknowledge the greatness of the Almighty God. By using qualitative descriptive methods, based on the results of research on the texts of the Koran and the Sunnah conducted by modern Muslim and non-Muslim scientists, who come from various fields of science, it is concluded that there is a harmony of scientific facts between the Koran and Hadith with science and this discovery reinforces the truth of both